Implementasi Pengembangan Kewirausahaan Lokal dan Penyaluran Bantuan Hewan Ternak Terhadap Masyarakat Melalui KKN Mahasiswa UIN Fatmawati Sukarno Bengkulu, di Dusun I, Desa Niur, Kecamatan Sukaraja, Kabupaten Seluma - Varizal, Aditya Gusti; Agustiani, Lola; Al-Fatih, M. Taskin; Khadafi, M. Ammar; Sumarni, Yenti (PPSDP Undergraduate Journal of Educational Sciences, 2024)
This article was examining the role or the involvement of students, especially KKN Group 76 UINFAS Bengkulu students, was carried out by 4 students from 2 faculties, namely the Sharia Faculty and the Islamic Economics and Business Faculty. In carrying out this service, the KKN 76 implemented 3 aspects, namely Religion and Education, Community Law, and Sharia Economics. This KKN service activity was carried out for 40 days in Hamlet I, Niur Village, District. Sukaraja, Kab. Seluma. This article aims to help the village community in improving the economy, the economic welfare of the community in Hamlet I Niur Village together with the village residents, Islamic youth at the mosque, and the Niur Village Youth Organization. In this scientific work article, qualitative research methods are used with a descriptive approach in the data collection process and research methods, namely by conducting field observations and describing the activities or programs of KKN 76 groups that have been implemented in Niur Village.